Elementy biblioterapii – propozycja dydaktyczna (Psychologia kliniczna dziecka) - Żurko, Magdalena (2016)
The article presents the concept of teaching classes of bibliotherapy for students specialized in the clinical child psychology. The study describes more precisely theoretical approaches explaining the mechanism of disorders of children and corresponding bibliotherapy’s elements (the therapy using literature, the therapy using stories, fairy relaxation). The study program enable students to select the appropriate methods and critical evaluation. The article presents the possibility of using the theory of positive disintegration of K. Dąbrowski in bibliotherapy based on a literary text. Program contents the training of treatment (therapy) the disorders and do not include psychoprofylaxis and health psychology.
Keywords: education of students; clinical child psychology; Kazimierz Dąbrowski; bibliotherapy in Poland; bibliotherapy